2020
DOI: 10.1007/s10439-020-02519-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiently Simulating an Endograft Deployment: A Methodology for Detailed CFD Analyses

Abstract: Numerical models of endografts for the simulation of endovascular aneurysm repair are increasingly important in the improvement of device designs and patient outcomes. Nevertheless, current finite element analysis (FEA) models of complete endograft devices come at a high computational cost, requiring days of runtime, therefore restricting their applicability. In the current study, an efficient FEA model of the Anaconda™ endograft (Terumo Aortic, UK) was developed, able to yield results in just over 4 h, an ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Then, the catheter was removed to let the device expand: the stent-graft was deployed at once and the free flow ring was not released as last, but simultaneously with all the stent struts. In particular, simulations with Nitinol modeled as linear elastic material ( E = E A = 57,500 MPa 13 , 16 , 21 , 29 ) or with PET as linear elastic material ( E = 1.84 MPa 18 , 20 , 33 and E = 1.84 GPa 24 ) were tested as well as the effect of the absence of the stent pre-stress. 18 , 19 , 33 Also, to investigate the stent-graft releasing phase, a condition of modified “virtual catheter” method was studied where the stent-graft was deployed gradually.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the catheter was removed to let the device expand: the stent-graft was deployed at once and the free flow ring was not released as last, but simultaneously with all the stent struts. In particular, simulations with Nitinol modeled as linear elastic material ( E = E A = 57,500 MPa 13 , 16 , 21 , 29 ) or with PET as linear elastic material ( E = 1.84 MPa 18 , 20 , 33 and E = 1.84 GPa 24 ) were tested as well as the effect of the absence of the stent pre-stress. 18 , 19 , 33 Also, to investigate the stent-graft releasing phase, a condition of modified “virtual catheter” method was studied where the stent-graft was deployed gradually.…”
Section: Methodsmentioning
confidence: 99%
“…12 For the stent component, some studies simplify the superelastic Nitinol behavior with a linear elastic material model with Young's modulus equal to the austenitic one. 13,16,21,29 In addition, a few works introduce the pre-stress field in the unloaded stent component. 7,11,17,19,34 This study aims at developing high-fidelity FE simulations to virtually reproduce the TEVAR procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the computational models were geometrically asymmetrical, phase shift of pressure and different flow splits at two iliac outlets may occur ( Grinberg and Karniadakis, 2008 ). Therefore, the flow split between two iliac branches in the models was regulated by the Windkessel model ( Kyriakou et al, 2020 ), where their RCR parameters were matched for 1 million times by trial-and-error method. The matching blood pressure was the iliac artery outlet blood pressure (100/80 mmHg) given in the previous literature ( Mills et al, 1970 ).…”
Section: Methodsmentioning
confidence: 99%
“…Matsagkas et al showed that the hemodynamic indexes of different laminating stents might significantly differ from the actual model ( Raptis et al, 2017b ). Finally, previous studies have proposed that the folds caused by the bending of stent grafts will affect the hemodynamics near the wall ( Prasad et al, 2012 ; Kyriakou et al, 2020 ). In vivo limb stents involve many curved parts, but the current models did not consider the impact of folds, which will be the focus of our future research.…”
Section: Limitationsmentioning
confidence: 97%